2020
DOI: 10.1007/s40944-020-00443-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery and Surgical Smoke, Decoding Fear and Ensuring Safety: Adaptations and Safety Modifications During COVID Pandemic

Abstract: The most fearful word starting from C, Cancer has now been replaced with COVID-19 owing to its associated physical, emotional and financial hardships as well as its social stigma. Never before we as medical fraternity been challenged to take care of patients and at the same time consider the safety of ourselves, family members and our fellow healthcare workers. Emotions and fear-driven treatments that are otherwise inefficacious may contribute to a false sense of security, unwarranted side-effects, divert reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In fact, in the Somashekhar et al ( 2020) study, it is reported that one of the main concerns about surgical intervention during the pandemic is the fear of surgical smoke (for reasons such as the risk of viral contamination and exposure to smoke) [29]. According to results of this study, operating room nurses experienced fear at the level of phobia due to Covid-19, since the Covid-19 phobia score was high (Table 3).…”
Section: Discussionmentioning
confidence: 58%
“…In fact, in the Somashekhar et al ( 2020) study, it is reported that one of the main concerns about surgical intervention during the pandemic is the fear of surgical smoke (for reasons such as the risk of viral contamination and exposure to smoke) [29]. According to results of this study, operating room nurses experienced fear at the level of phobia due to Covid-19, since the Covid-19 phobia score was high (Table 3).…”
Section: Discussionmentioning
confidence: 58%
“…20 Similar to our study, Somashekhar et al demonstrated safe laparoscopic surgery using an extra port trocar for smoke evacuation during laparoscopy, which was connected with tubing to a water seal container containing 4% sodium hypochlorite solution. 25 Pawar et al performed 12 colorectal cancer surgeries by laparoscopic methods by using HEPA filter in all COVID positive patients using full PPE. He reported that laparoscopic surgery can be safely performed.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Instead of Heated water, an underwater seal container containing 4% sodium hypochlorite solution has also been recommended for the evacuation of smoke during laparoscopic surgery. 25,26 So this study was aimed to observe the effects of the use of filtration System (Heat and Moisture exchanger (HME) filter along with desufflation in underwater seal bag containing 5% sodium hypochlorite solution) in laparoscopic surgery on surgery staffs to reduce the cross-contamination and transmission of covid-19.…”
mentioning
confidence: 99%
“…N95 respirators are a type of personal protective equipment (PPE) designed specifically to provide a higher level of respiratory protection [ 48 ]. These respirators provide a tight seal to the face and can filter out at least 95 percent of airborne particles, including smaller particles and aerosols [ 49 ].…”
Section: Reviewmentioning
confidence: 99%